Pengaruh Geometri Jalan Terhadap Konsumsi Bahan Bakar pada Kegiatan Penambangan Batubara PT Pacific Global Utama di Kecamatan Tanjung Agung, Kabupaten Muara Enim, Provinsi Sumatera Selatan - Vallen Aurelio Gemilang; Zaenal; Indra Karna Wijaksana (Bandung Conference Series: Mining Engineering, 2023)
Abstract. PT Pacific Global Utama is a company engaged in the coal mining industry. Coal mining activities use digging-loading and hauling equipment using the Komatsu PC400 Lc Excavator and the Volvo A40F Articulated Dumptruck. There is a company Fuel Ratio target of 0.4 liters/BCM, which was not achieved as a result of the road geometry not conforming to standards. Efforts to reduce the Fuel Ratio are by studying the geometry of the haul road and making efforts to improve the haul road in order to increase the efficiency of fuel use for the transportation equipment. The purpose of this study is to optimize the mine road geometry which affects fuel consumption. The theory used in this study is based on AASHTO, and Minister of Energy and Mineral Resources Decree 1827K No. 30 of 2018. Production calculations are obtained by taking direct coal mining activities, while road geometry is measured using a roll meter, compass, and GPS, and validated using a map. Contours made using drones. The production of the digging equipment was 225.68 BCM/hour while the means of transportation were 225.43 BCM/hour, with the fuel consumption of the digging and loading equipment being 39.41 liters/hour/tool and the transportation equipment being 23.69 liters/hour/equipment. This study also examines the Fuel Ratio (FR) and Fuel Cost (FC) of transportation equipment before and after the road improvement recommendations, the actual FR is 0.52 liters/BCM with an actual FC of RP 2,029,885.51/shift/tool. Recapitulation of road repairs can increase the production of transportation equipment to 298.54 BCM/hour. There are changes in FR and FC in the road repair recommendations where FR becomes 0.397 liters/BCM and FC becomes RP 1,532,814.74/shift/equipment. Abstrak. PT Pacific Global Utama adalah salah satu perusahaan yang bergerak di bidang industri pertambangan batubara. Kegiatan penambangan batubara menggunakan alat gali-muat dan angkut memakai Excavator Komatsu PC400 Lc dan Articulated Dumptruck Volvo A40F. Terdapat target Fuel Ratio perusahaan sebesar 0,4 liter/BCM, yang tidak tercapai akibat dari geometri jalan yang tidak sesuai dengan standar. Usaha untuk menurunkan Fuel Ratio tersebut dengan cara mengkaji geometri jalan angkut dan melakukan upaya perbaikan jalan angkut guna meningkatkan efisiensi penggunaan bahan bakar alat angkut. Tujuan dari penelitian ini yaitu untuk mengoptimalkan geometri jalan tambang yang berpengaruh terhadap konsumsi bahan bakar. Teori yang digunakan pada penelitian ini didasarkan pada AASHTO, dan Kepmen ESDM 1827K No.30 tahun 2018. Perhitungan produksi didapatkan dengan pengambilan langsung kegiatan penambangan batubara, sedangkan untuk geometri jalan diukur menggunakan alat bantu roll meter, kompas, dan GPS, serta divalidasi menggunakan peta kontur yang dibuat dengan menggunakan drone. Produksi alat gali-muat sebesar 225,68 BCM/jam sedangkan alat angkut 225,43 BCM/jam, dengan konsumsi bahan bakar alat gali-muat 39,41 liter/jam/alat dan alat angkut 23,69 liter/jam/alat. Penelitian ini juga mengkaji Fuel Ratio (FR) dan Fuel Cost (FC) alat angkut sebelum dan setelah rekomendasi perbaikan jalan, FR aktual sebesar 0,52 liter/BCM dengan FC aktual sebesar RP 2.029.885,51/shift/alat. Rekapitulasi perbaikan jalan dapat meningkatkan produksi alat angkut menjadi 298,54 BCM/jam.Terdapat perubahan FR dan FC pada rekomendasi perbaikan jalan dimana FR menjadi 0,397 liter/BCM dan FC menjadi RP 1.532.814,74/shift/alat.